Dynamic Modeling and Analysis of Micro-Video Teaching System Based on Cloud Computing in College English Teaching - Ying Chen (Discrete Dynamics in Nature and Society)
The era is developing and the society is improving. The application research of computer technology in the field of education is a hot topic at present. The cultivation of talents required the training of schools and teachers. How to cultivate talented person who meets the needs of society lied in the comprehensive ability of teaching in colleges and universities, so the college English education professional grammar teaching model is studied based on dynamic programming algorithm. After a brief overview of the dynamic rule algorithm, an algorithm for evaluating English grammar learning in colleges and universities is designed by using dynamic algorithm. The algorithm is composed of dynamic rule algorithm, language processing technology, and regular expression. In the subsequent experiments, it is proved that the algorithm has a good evaluation effect and can meet the actual application requirements.